EVALUATING USER’S LEVEL OF SATISFACTION WITH THE CHINESE STUDIES COLLECTION HELD AT AN ACADEMIC LIBRARY - Chia, Yip Ping; N.N., Edzan (Malaysian Journal of Library and Information Science, 2017)
A user assessment study was conducted to evaluate the users’ level of satisfaction with the Chinese studies collection at the University of Malaya Library. The respondents were library professionals, faculty members, undergraduate and postgraduate students at the Department of Chinese Studies, University of Malaya. A total of 135 responses were received with a response rate of 77.5%. The results indicated that the undergraduates of years 2 and 3 and the postgraduates were less satisfied with the collection and services compared with the undergraduates of year 1, faculty members and library professionals. Results showed that there is no significant gap between the performance evaluation by library professionals and library users’ expectations in the level of satisfaction with the information sources available between the library professionals and the respondents from the Department of Chinese Studies at the university.